The Dynamic Effects of Works Councils on Labor Productivity: First Evidence from Panel Data - Steffen Müller; Jens Stegmaier (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2015)
We estimate dynamic effects of works councils on labor productivity using newly available information from West German establishment panel data. Conditioning on plant fixed effects and control variables, we find negative productivity effects during the first five years after council introduction, but a steady and substantial increase in the councils' productivity effect thereafter. Given the frequently reported positive correlation between council existence and plant productivity, this finding supports causal interpretations.
urn:nbn:de:gbv:3:2-48633
Keywords: D24; J53; 330; non-union worker representation; works council; labor productivity; dynamic effects